An evidence-based bundle improves the quality of care and outcomes of patients with candidaemia. (9th December 2019) - Cardozo, Celia; Cuervo, Guillermo; Salavert, Miguel; Merino, Paloma; Gioia, Francesca; Fernández-Ruiz, Mario; López-Cortés, Luis E; Escolá-Vergé, Laura; Montejo, Miguel; Muñoz, Patricia; Aguilar-Guisado, Manuela; Puerta-Alcalde, Pedro; et al.
Abstract: Background: Candidaemia is a leading cause of bloodstream infections in hospitalized patients all over the world. It remains associated with high mortality. Objectives: To assess the impact of implementing an evidence-based package of measures (bundle) on the quality of care and outcomes of candidaemia. Methods: A systematic review of the literature was performed to identify measures related to better outcomes in candidaemia. Eight quality-of-care indicators (QCIs) were identified and a set of written recommendations (early treatment, echinocandins in septic shock, source control, follow-up blood culture, ophthalmoscopy, echocardiography, de-escalation, length of treatment) was prospectively implemented. The study was performed in 11 tertiary hospitals in Spain. A quasi-experimental design before and during bundle implementation (September 2016 to February 2018) was used. For the pre-intervention period, data from the prospective national surveillance were used (May 2010 to April 2011). Results: A total of 385 and 263 episodes were included in the pre-intervention and intervention groups, respectively. Adherence to all QCIs improved in the intervention group. The intervention group had a decrease in early (OR 0.46; 95% CI 0.23–0.89; P = 0.022) and overall (OR 0.61; 95% CI 0.4–0.94; P = 0.023) mortality after controlling for potential confounders. Conclusions: Implementing a structured, evidence-based intervention bundle significantly improved patient care and early and overall mortality in patients with candidaemia. Institutions should embrace this objective strategy and use the bundle as a means to measure high-quality medical care of patients.